Photon shielding competence of concrete doped CuO for gamma shielding applications - Hudu, Salisu; Mustapha, Idris M.; Bello, Sulayman M.; Halimatu, Abdullahi S.; James, Iwa S.; Aisha, Mohammed A.; Ubaidullah, Ahmad (Universitas Sebelas Maret, 2024)
In this study, photon attenuation parameters of concrete doped CuO, were determined and their application as shielding material were discussed. The WinXCOM software was used to determine the mass attenuation coefficient (MAC) of the concrete doped CuO samples (0, 20, 40 60 and 100 wt% CuO content) for the energy range (0.015-15MeV). The linear attenuation coefficient, half value layer (HVL), mean free path (MFP), and effective atomic number (Zeff) were calculated from the MAC values. The MAC values of the samples decreases rapidly up to 0.12 MeV, and beyond 0.12 MeV, Compton scattering becomes effective at intermediate energies. The LAC value vary with energy in similar way as MAC. The calculated HVL and MFP were observe to decline as the CuO doping of the glasses increased which accounts for the three photon interaction mechanisms effectiveness in the variation of HVL and MFP values with energy. The Zeff shows minimal variation as the energy increases in all the concrete doped CuO samples. It can be concluded that doping CuO with concrete can greatly enhance the gamma shielding ability of the sample.